CD8αα Expression Marks Terminally Differentiated Human CD8+ T Cells Expanded in Chronic Viral Infection - Walker, Lucy J.; Marrinan, Elizabeth; Muenchhoff, Maximillian; Fergusson, Joannah R.; Kloverpris, Henrik; Cheroutre, Hilde; Barnes, Eleanor; Goulder, Philip; Klenerman, Paul (Frontiers in Immunology, 2013)
The T cell co-receptor CD8αβ enhances T cell sensitivity to antigen, however studies indicate CD8αα has the converse effect and acts as a co-repressor. Using a combination of Thymic Leukaemia antigen (TL) tetramer, which directly binds CD8αα, anti-CD161 and anti-Vα7.2 antibodies we have been able for the first time to clearly define CD8αα expression on human CD8 T cells subsets. In healthy controls CD8αα is most highly expressed by CD161 “bright” (CD161++) mucosal associated invariant T (MAIT) cells, with CD8αα expression highly restricted to the TCR Vα7.2+ cells of this subset. We also identified CD8αα-expressing populations within the CD161 “mid” (CD161+) and “negative” (CD161-) non-MAIT CD8 T cell subsets and show TL-tetramer binding to correlate with expression of CD8β at low levels in the context of maintained CD8α expression (CD8α+CD8βlow). In addition, we found CD161-CD8α+CD8βlow populations to be significantly expanded in the peripheral blood of HIV-1 and hepatitis B (mean of 47% and 40% of CD161- T cells respectively) infected individuals. Such CD8αα expressing T cells are an effector-memory population (CD45RA-, CCR7-, CD62L-) that express markers of activation and maturation (HLA-DR+, CD28-, CD27-, CD57+) and are functionally distinct, expressing greater levels of TNF-α and IFN-γ on stimulation and perforin at rest than their CD8α+CD8βhigh counterparts. Antigen-specific T cells in HLA-B*4201+HIV-1 infected patients are found within both the CD161-CD8α+CD8βhigh and CD161-CD8α+CD8βlow populations. Overall we have clearly defined CD8αα expressing human T cell subsets using the TL-tetramer, and have demonstrated CD161-CD8α+CD8βlow populations, highly expanded in disease settings, to co-express CD8αβ and CD8αα. Co-expression of CD8αα on CD8αβ T cells may impact on their overall function in-vivo and contribute to the distinctive phenotype of highly differentiated populations in HBV and HIV-1 infection.